Network Infrastructure Design Of Gigabit Passive Ethernet Technology At Dehasen University, Bengkulu - Khairil Khairil; Juju Jumadi; Ila Yati Beti (International Journal of Artificial Intelligence Research, 2023)
The development of information technology has significantly increased the demand for reliable and stable internet network infrastructure, especially in higher education institutions. Universities require efficient network systems to support academic activities, digital learning, research, and administrative services. This research aims to design a network infrastructure using Gigabit Passive Ethernet Network (GPEN) technology at Universitas Dehasen Bengkulu. The previous network infrastructure relied on wireless radio point-to-point connections which often experienced interference caused by obstacles such as buildings, trees, and weather conditions. The proposed GPEN-based infrastructure is expected to provide a more stable and efficient network connection compared to the previous system. The research method used is Research and Development (R&D), which includes observation, literature study, and laboratory testing. Network design is implemented using MikroTik devices such as NetPower, GPEN11, and GPeR to extend Ethernet connectivity. The results of this study show that the GPEN network implementation provides better bandwidth stability, reduces interference problems, and improves overall network performance. Therefore, the GPEN-based infrastructure can be considered an effective solution for improving campus network connectivity at Universitas Dehasen Bengkulu